PERSEPSI GURU TERHADAP KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM MENGELOLA GURU PADA SMA SWASTA KECAMATAN PADANG BARAT KOTA PADANG - Eka Syafitri (Universitas Negeri Padang, 2017)
The purpose of this research was look information about the teacher perception of managerial competence head master in managing teacher onprivate senior hight school western Padang district. This is a descriptive research. The population is 328teachers and research sample is 71 teachers that taken by cluster random sampling and stratified propotional random sampling.The instrument of this research was a questionnaire with Likert scale models that had tested for validity and reliability. Data analyzed using the average (mean)formula. The resultsof this research show teachers perception of managerial competence head master in managing theacher on private senior hight school (SMAS) western Padang districtin Padang city stay in good category with an average score 4,17 become 83,38 percent.Keywords: Perception, managerial competence